DON QUIXOTE : THE CRAZY ADVENTURES OF A KNIGHT-IN-TRAINING - Cervantes, Miguel De; Bradie, Michael Robert (Singapore : WS Education, an imprint of World Scientific Publishing Co. Pte. Ltd., 2022)
Alonso is an old man who is obsessed with stories of heroism. So, he reinvents himself as Don Quixote, knight-in-training! Accompanied by his servant-turned-squire, Sancho, as well as his trusty old horse Rosinante, he sets off on many crazy adventures. Join this wacky knight as he attempts to battle giants that aren't giants and saves maidens who might not want to be saved!
Keywords: English fiction; Adventures -- Juvenile fiction